SIKAP DAN KEPUASAN KONSUMEN TERHADAP PRODUK TEMPE BERMEREK DAN TEMPE TANPA MEREK DI BANDAR LAMPUNG - Ivo Revita; Teguh Endaryanto; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to determine the consumer characteristics, consumer attitudes, and consumer satisfaction of branded and unbranded tempeh in Bandar Lampung. The research is conducted at Pasir Gintung Market. The research samples are 78 people chosen by nonprobability sampling. The data is analyzed by descriptive qualitative, The Multi-attribute Fishbein Models, Customer Satisfaction Index and Importance Performance Analysis. The results showed that the branded and unbranded tempeh consumers were mostly housewives aged 36-50 years old with family income ranging from Rp3,500,000.00-5,000,000.00/month. More than 50 percent consumers were Javanese living in distance of 0-3 km from the market and bought tempeh in the morning. The results showed that consumer gave the highest attitude scored to the cleanliness attribute of branded tempeh and the taste attribute of unbranded tempeh. The level of consumer satisfaction of branded tempeh and unbranded tempeh were 79.39 percent and 80.47 percent included to the satisfied categories. The performance of product attributes of branded tempeh has beed in accordance with the wishes of consumers. Whereas, the attributes of product cleanliness and product purity of the unbranded tempeh was needed to be improved.Key words: attitude, consumers, satisfaction, tempeh